2018
DOI: 10.21577/0103-5053.20180242
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seasonality and Sunlight Effects on Rollinia mucosa Leaves Fingerprint

Abstract: Rollinia mucosa fruit has generated great interest due to the presence of bioactive compounds, which exhibit promising biological activities. Fingerprinting analytical techniques, chromatographic-diode array detection (DAD), infrared, mass spectrometric, 1 H and 13 C nuclear magnetic resonance (NMR) spectra, associated with chemometric analysis and mixture design, were used to determine chemical discriminations of sun-exposed and self-shaded leaves of Rollinia mucosa in each of the four seasons. Sunlit leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Considering extraction to be the probable limiting step of this analysis, our group has been focusing on metabolite extractions from different plant matrices using statistical mixture designs. [33][34][35][36][37][38][39] The objective of the research reported here is to develop an analytical fingerprinting procedure to study metabolite abundance changes in Coffea arabica L. samples suffering water-deficit stress. An integrated chemometrics approach involving statistical mixture design and factor analysis applied to proton nuclear magnetic resonance ( 1 H NMR) data combined with confirmatory mass spectrometric evidence clarifies the metabolic adaptation process owing to this environmental stress.…”
Section: Introductionmentioning
confidence: 99%
“…Considering extraction to be the probable limiting step of this analysis, our group has been focusing on metabolite extractions from different plant matrices using statistical mixture designs. [33][34][35][36][37][38][39] The objective of the research reported here is to develop an analytical fingerprinting procedure to study metabolite abundance changes in Coffea arabica L. samples suffering water-deficit stress. An integrated chemometrics approach involving statistical mixture design and factor analysis applied to proton nuclear magnetic resonance ( 1 H NMR) data combined with confirmatory mass spectrometric evidence clarifies the metabolic adaptation process owing to this environmental stress.…”
Section: Introductionmentioning
confidence: 99%
“…Data sets of mixture design–fingerprints, using different solvents in the extraction, have been analyzed simultaneously with PCA, common dimensions analysis (ComDim), exploratory factor analysis (EFA), and partial least-squares-discriminant analysis (PLS-DA), among others, as a procedure to maximize the range of metabolites analyzed simultaneously in mathematical modeling. This procedure has been successfully applied for various plant materials, such as Coffea arabica leaves and beans, , yerba mate leaves, Rollinia mucosa leaves, Mikania laevigata leaves, and several other plant species.…”
Section: Introductionmentioning
confidence: 99%
“…The Rollinia species that have aroused interest include the “biribá” tree ( Rollinia mucosa [Jacq.] Baill), a tropical species native to the West Indies and South and Central America (Afonso et al, 2019; Soares et al, 2014) that produces the “biribá,” an edible fruit of yellow color when ripe, with a globose shape, weighing up to 1.3 kg, and whose bark has protrusions in the form of flexible pointed thorns. The mucilaginous “biribá” pulp has a whitish to cream color, pleasant aroma, and sweet flavor, containing many dark‐colored seeds (Soares et al, 2014; Souza et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This species is very popular in countries such as Brazil, Mexico, Bolivia, and Venezuela (Afonso et al, 2019), justifying its cultivation in the neotropics (Soares et al, 2014). According to Lorenzoni et al (2014), the great acceptance of this fruit makes the “biribá” tree a potential crop for orchards, providing an economic return in at most 5 years after planting.…”
Section: Introductionmentioning
confidence: 99%